2004
DOI: 10.1177/105381510402600206
|View full text |Cite
|
Sign up to set email alerts
|

Types and Patterns of Professional-Family Talk in Home-Based Early Intervention

Abstract: This study examined the process of communication within the professional-family relationship by identifying and describing the types and patterns of talk during interactions between 15 families of young children with developmental delays and their respective early interventionists. Videotaped interactions of routine home visits were coded using a computerized coding system designed to record and analyze professional-family talk related to direct and indirect communication approaches. The tapes yielded 13,145 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
(23 reference statements)
1
13
0
1
Order By: Relevance
“…Investigation of the actual interactions between parents and providers was found in only one study, which analyzed the type of communications that occurred during early intervention home visits (Brady, Peters, Gamel-McCormick, & Venuto, 2004). Home visit intervention sessions were videotaped and analyzed using a previously developed tool.…”
mentioning
confidence: 99%
“…Investigation of the actual interactions between parents and providers was found in only one study, which analyzed the type of communications that occurred during early intervention home visits (Brady, Peters, Gamel-McCormick, & Venuto, 2004). Home visit intervention sessions were videotaped and analyzed using a previously developed tool.…”
mentioning
confidence: 99%
“…Estes resultados divergem dos que são reportados nos estudos internacionais que referimos (Brady et al, 2004;Campbell & Sawyer, 2007;Keilty, 2008;McBride & Peterson, 1997;Peterson et al, 2007;Rydley & O'Kelley, 2008;Turnbull et al, 2007), que revelam ser a maioria das interacções entre os profissionais e as crianças, mantendo-se as famílias, frequentemente, não envolvidas. Divergem, também dos dados reportados por Marques (2003) num estudo com método e medidas semelhantes, que mostram uma intervenção muito centrada no bebé, não promovendo a autonomia da família.…”
Section: Discussionunclassified
“…Chopra and French (2004) noted that parents of children with disabilities are partners with school professionals ''in the care, treatment, and education of their children' ' (p. 240). However, research indicates that the extent to which parents actually participate in exchanging feelings, ideas, and information varies (Brady et al, 2004;Crais et al, 2006;Kjaerbeck, 2008;Pappas et al, 2008). For instance, Brady et al (2004) found that family participation in early intervention discussions were significantly and positively correlated with professionals accepting ideas, praising, and encouraging.…”
Section: Considering Familiesmentioning
confidence: 92%
“…However, research indicates that the extent to which parents actually participate in exchanging feelings, ideas, and information varies (Brady et al, 2004;Crais et al, 2006;Kjaerbeck, 2008;Pappas et al, 2008). For instance, Brady et al (2004) found that family participation in early intervention discussions were significantly and positively correlated with professionals accepting ideas, praising, and encouraging. However, questions asked by professionals were not significantly correlated with family member talk, with 96% of professionals' questions being closed-ended.…”
Section: Considering Familiesmentioning
confidence: 92%
See 1 more Smart Citation